3D printed polylactic acid/gelatin-nano-hydroxyapatite/platelet-rich plasma scaffold for critical-sized skull defect regeneration - Bahraminasab, Marjan; Doostmohammadi, Nesa; Talebi, Athar; Arab, Samaneh; Alizadeh, Akram; Ghanbari, Ali; Salati, Amir (Biomedical engineering online, 2022)
Background Three-dimensional (3D) printing is a capable approach for the fabrication of bone tissue scaffolds. Nevertheless, a purely made scaffold such as polylactic acid (PLA) may suffer from shortcomings and be restricted due to its biological behavior. Gelatin, hydroxyapatite and platelet-rich plasma (PRP) have been revealed to be of potential to enhance the osteogenic effect. In this study, it was tried to improve the properties of 3D-printed PLA scaffolds by infilling them with gelatin-nano-hydroxyapatite (PLA/G-nHA) and subsequent coating with PRP. For comparison, bare PLA and PLA/G-nHA scaffolds were also fabricated. The printing accuracy, the scaffold structural characterizations, mechanical properties, degradability behavior, cell adhesion, mineralization, systemic effect of the scaffolds on the liver enzymes, osteocalcin level in blood serum and in vivo bone regeneration capability in rat critical-sized calvaria defect were evaluated. Results High printing accuracy (printing error of < 11%) was obtained for all measured parameters including strut thickness, pore width, scaffold density and porosity%. The highest mean ultimate compression strength (UCS) was associated with PLA/G-nHA/PRP scaffolds, which was 10.95 MPa. A slow degradation rate was observed for all scaffolds. The PLA/G-nHA/PRP had slightly higher degradation rate, possibly due to PRP release, with burst release occurred at week 4. The MTT results showed that PLA/G-nHA/PRP provided the highest cell proliferation at all time points, and the serum biochemistry (ALT and AST level) results indicated no abnormal/toxic influence caused by scaffold biomaterials. Superior cell adhesion and mineralization were obtained for PLA/G-nHA/PRP. Furthermore, all the developed scaffolds showed bone repair capability. The PLA/G-nHA/PRP scaffolds could better support bone regeneration than bare PLA and PLA/G-nHA scaffolds. Conclusion The PLA/G-nHA/PRP scaffolds can be considered as potential for hard tissue repair.